Asesmen Potensi Inteligensi Pada Anak Usia Dini - Laily, Nadhirotul; Sholichah, Ima Fitri (Efektor, 2021)
The development of learning based on the potential for early childhood intelligence is very limited. The purpose of this study is to describe the potential intelligence of early childhood. The method used is a descriptive qualitative approach. 5 students are the subjects in this study. The instruments used were intelligence tests, observation, and documentation. Data analysis in this study is an interactive analysis model. The results showed that 5 students (2 boys and 3 girls) had IQ abilities from below average to superior categories. Based on this intelligence assessment, it can be a reference for Early Childhood Education (PAUD) institutions to design a curriculum based on child development and in terms of the potential for intelligence to improve the teaching and learning process. The use of child development-based education can improve children's abilities to support future development.